Rancang Bangun Prototipe Tempat Pencucian Mobil Otomatis Berbasis Programmable Logic Controller (PLC Outseal) Dan Internet Of Things (IOT) - Sitinjak, Heinz Valtin; Ginting, Ferdinan Gunanta; Rianda, Rianda; Sufandi, Muhammad Ridhwan; Hasan, Hasan; Yuniarto, Wendhi (Jurnal ELIT, 2024)
In the current era of globalization, technology has become an integral part of people's lives. Automatic car washing is one example, offering services with the best quality, short processing times, and high efficiency. Control devices such as the PLC Outseal Mega V2, proximity sensors, solenoid control valves, gearbox motors, limit switches, fans, and buzzers are used in the automatic car washing process, resulting in cleaner and more well-maintained vehicles. Cars are very popular all over the world. Every year, various car manufacturers produce interesting and attractive car variations at affordable prices for people from different walks of life, which is the result of automotive technological advancements that drive an increase in the number of cars produced every year. As the demand for car wash services continues to increase along with the growth in the number of vehicles available in the city, the car wash business is a good investment opportunity in Pontianak